Parental Involvement in Curricular Performance of Students at Risk - Dungca, Jasley L.; Agbayani, Gabriel Yvonne; Muñoz, Avril Laine G.; Carreon, Brian Mikko D.; Antonio, Faye D.; Tiqui, Jenna Anne S.; Castro, Aikee M.; Galang, John Renus F. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
Parental involvement plays an important role in the academic performance of at-risk learners facing educational challenges. However, many parents struggle to contribute effectively due to various challenges, such as limited educational backgrounds, busy schedules, and personal commitments. This study aims to describe the parental involvement in the academic performance of at-risk learners, specifically focusing on involvement, success, and support within the school. This study uses a Mixed-methods sequential explanatory design. The study involves quantitative analysis supplemented by qualitative insights obtained through standardized questionnaires and interviews. Purposive sampling was employed to select 50 parents as respondents, while 8 participants were chosen using a homogeneous sampling technique to represent outliers. Results indicate that active parental involvement positively improves academic outcomes, including behavior, attendance, and grades. Conversely, learners with less engaged parents tend to show limited progress in their academic performance. Lack of financial resources poses significant challenges, but scholarships lessen burdens, ensuring access to education for all. This study underscores the importance of parental support beyond academics, creating helpful learning environments, and fostering strong development. Understanding parental challenges can enhance strategies to improve learners’ behavior and academic performance. Overall, parental involvement is an important factor in promoting academic success and preparing learners for future opportunities.